Implementation of Model Strengthening Religious Character Education and Nationalists at Muhammadiyah Plus Elementary School City of Salatiga Academic Year 2017/2018 - Ainul Huri; Marwanto Marwanto (MUDARRISA: Jurnal Kajian Pendidikan Islam, 2019)
The Character-Building Reinforcement (PPK) in Muhammadiyah Plus Elementary School of Salatiga is to strengthen the students being religious and nationalist. The aim of this research is to identify the application and the success of the Character Building Reinforcement; religious and nationalist in Muhammdiyah Plus Elementary School of Salatiga year 2017/2018. This is qualitative descriptive research, the data is taken from the interview, observation, and documentation. The data analysis technique is using data collection, data reduction, data display, verification, and conclusion confirmation. The result is the application of the implementation model of Character Building Reinforcement; religious and nationalist in Muhammadiyah Plus Elementary School of Salatiga year 2017/2018 is applied in academic, non academic, and self-development, whereas the success in other program and school wisdom are 1) Character-based program as a prime program to the value of religious and nationalist habituation. 2) The culture of the school to characterize the students through four things, they are routines, spontaneous activities, exemplary, and conditioning. 3) Character learning or Nobel character model of the students is holistic, integrated, and balanced according to graduate competence standard, through simple habituations in the classroom. 4) Active participation of the community to build good communication with public and private institutions and the local community. 5) Parents' involvement as the stakeholder makes the parents be active in the implementation of the Character Building Reinforcement in Muhammadiyah Plus Elementary School of Salatiga, especially in religious and nationalist education.